In vitro evaluation of the microhardness and porosity of two photopolymerizable composite resins - Caroline Bezerra de Souza; Basilio Rodrigues Vieira; Frederico Barbosa de Sousa; Eugenia Livia de Andrade Dantas; Millena Mangueira Rocha; José Henrique de Araújo Cruz; Luanna Abílio Diniz Melquíades de Medeiros; Gymenna Maria Tenório Guenes (Editorial Ciencias Médicas, 2020)
Introduction: Scientific studies about the physical and mechanical properties of composite resins are increasingly needed in view of the wide variety of products available in the market today, resulting from the increase in their demand for dental care purposes, with a preference for minimally invasive preparations aimed at restoring the esthetic and functional characteristics of the treated element. Objective: Evaluate and compare the microhardness and porosity of the photopolymerizable composite resins Filtek Z350 XT and Zirconfill Technew. Methods: Ten test bodies were developed per sample (n= 10) and subjected to Vickers microhardness and porosity testing by computerized microtomography. Results: With respect to the presence of porosity, expressed in percentages, the Filtek group had the lowest mean values. When compared statistically, the two groups showed a statistical difference (p= 0.019) with a high effect magnitude. Regarding microhardness, the Filtek group had the highest mean values. Statistical comparison did not find any difference between the groups (p> 0.05). Conclusions: Porosity was significantly different in the groups studied, the Filtek Z350XT group exhibiting the lowest percentage. However, the groups did not show any statistical difference concerning microhardness, despite the fact that the Filtek Z350XT group had a higher mean value.